Laju Pemampatan Tanah Gambut melalui Pengujian Konsolidasi Primer - Tifani, Efan (Departemen Teknik Sipil dan Lingkungan IPB, 2019)
On the very soft soil conditions that are easily compressed and thick like peat soil, initial loading is required by first loading the soil, the aim is to increase the carrying soil bearing capacity and reduce the settlement in primary consolidation before permanent construction of civil buildings is carried out, this method is known as preloading. Based on this, it is necessary to carry out a primary consolidation test using an oedometer to determine the rate of compression of the peat soil and how much reduction (consolidation) occurs using the square root of time method. Testing of the peat soil compression rate is carried out as much as 6 times of loading and 2 times of unloading in based on gdmaks and OMC conditions. From the test results, it is found that the compression that occurs in peat soil is very large at the beginning of loading, then the compression is smaller in stage during 6 times of loading, this shows that peat soil has a very high compression and compressibility rate at the beginning of loading at time t90 with the resulting curve linear.Keywords: Peat Soil, Compression, Loading Unloading, Consolidation